In Vitro Gas Production Test: towards Rapid Nutritional Evaluation of Roughages for Ruminant Feeding - M Sembiring; A.S.H. Baba (PT FORMOSA CENDEKIA GLOBAL, 2022)
The gas production in vitro method was used to evaluate the degradability and gas production of browse plants in the absence or presence of polyethylene glycol 8,000 (PEG). Substrates (leguminous and browse plants; 500mg) were incubated for 24h and the accumulated gas produced recorded. The incubation contents of the syringes were transferred into nylon bags and the undegraded residues weighed after washing and drying to constant weight (SNB method). Substrates were also incubated in the rumen in nylon bags for 24 h to determine in sacco degradability. Gas production ranged between 10.3 to 64.4ml whereas the dry matter degradability ranges between 27.3 and 70.9%. Addition of PEG, which minimised the inhibitory effects of tannin on microbial fermentation resulted in an increase in both gas production and degradability in vitro, which ranged from 25.7 to 64.2 ml and 34.2 to 75.0%, respectively. Correlation analysis of the DM degradability estimated by the SNB method and in sacco method was better in presence of PEG (y= 0.71x + 14.9; r2 = 0.92) as compared to absence of PEG (y= 0.59x + 15.0; r2 = 0.72). Partitioning factor (PF) of substrate to gas, which was expressed as mg DM degraded/ml gas, reflects the variation in microbial biomass yield. The PF figures varied from 4.94 -11.05 to PF+PEG values of 4.74-6.84 upon the addition of PEG. The present study showed that presence of tannin has a potentially beneficial effect to protein nutrition of the host animal by altering partitioning of nutrients towards more microbial yield rather than short chain fatty acids. PF values of browse plants determined both on the absence and presence of PEG may indicate the relative importance of tannins in different plant species on substrate degradability and partitioning of nutrients.